Effects of compressibility and guiding field on the Kelvin–Helmholtz instability in weakly reversed magnetic shear configurations - Z. Li; X. Q. Wang; J. Huang; J. Shao; Y. Luo; Y. Xu; H. F. Liu; H. Liu (AIP Advances, 2022)
The effects of compressibility and guiding field on the Kelvin–Helmholtz (KH) instability in a double resonant surface system are numerically investigated by using a compressible magnetohydrodynamics model. The linear growth rate and the nonlinear saturation amplitude are analyzed for different parameters. A transition from double tearing modes to the KH instability occurs depending on the compressibility and guiding field with a weak magnetic shear. These results may deepen our understanding of the properties of the KH instability with double resonant surfaces in both space and laboratory plasmas.